Karakteristik Minyak Zaitun dan Minyak Goreng Kelapa Sawit sebagai Minyak untuk Transformator - Gema Ramadhona; T Haryono (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2013)
Transformer insulating oil still commonly used in Indonesia is Shell Diala B pertamina production derived from petroleum. Vegetable oils (olive oil, palm cooking oil, and a mixture of both) to be known as the suitability for transformer oil were used in this study. Vegetable oils have advantages over petroleum that is renewable, sustainable, not toxic, biodegradable, and environmentally friendly. Parameters measured and tested were the value of breakdown voltage, at a temperature of 28 oC to 90 oC with each increment of 20 oC, flash point, pour point and viscosity. The test results showed that the pure olive oil at 28 oC had the most high breakdown voltage and fit for use as transformer oil because it has a breakdown voltage of 43 kV, over the test method standard of IEC 156 i.e. ≥ 30 kV/2.5 mm. On all the oil, the temperature rise will cause an increase in the value of breakdown voltage, it is due to the air bubbles in the oil reduced. At a temperature of 90 oC, olive oil still has the highest value with the value of breakdown voltage is 52.31 kV. The most high flash point on pure palm cooking oil is 324 oC over the test method standard of IEC 296 A (> 140 oC). The lowest pour point in the pure olive oil is at -12 oC, under the test method standard of IEC 296 (≤ -30 oC). While the viscosity of the oil composition has almost the same value of about 40 cSt, under the test method standard of IEC 296 class 1 (≤ 11 cSt).